Penerapan Lembar Kerja Peserta Didik Berbasis Etnosains untuk Meningkatkan Hasil Belajar di SMP Negeri 8 Banda Aceh - Muslimatul Walidah*; Evendi Evendi; Hafnati Rahmatan (Jurnal Pendidikan Sains Indonesia, 2023)
Ethnoscience knowledge is still underdeveloped in science learning. One of the ethnoscience knowledge that has been passed down from generation to generation in Aceh is smong which has a close relationship with disaster risk reduction. SMP Negeri 8 Banda Aceh is one of the areas that has been affected by the earthquake and tsunami so that smong knowledge needs to be introduced to students. The purpose of this study was to determine the differences in learning outcomes and student responses. The population of this study were all seventh grade students of SMP Negeri 8 Banda Aceh. The sample was selected by random sampling, namely 71 students divided into experimental and control classes. Research parameters are learning outcomes measured through pretest-posttest and student responses through questionnaires. Based on data analysis, there are significant differences in student learning outcomes between the control and experimental classes after using ethnoscience-based worksheets as indicated by the value of Sig. (2-tailed) 0.05. The percentage of student responses obtained was 89.58 with a very good category. The results obtained prove that the use of ethnoscience-based worksheet can improve student learning outcomes and get a positive response